3ds max 6. (Architectural Record, 2003)
This article introduces digital tools for managing, learning and designing architecture. The newest release of this high-end visualization software offers an integrated ray-tracing rendering tool, a new event-driven particle system, and improved compatibility with Autodesk design software, including an integrated workflow with VIZ to share VIZ Render.